The infiltration rate of developed and undeveloped area in Universiti Malaysia Pahang - Nural Fatiha, Rosle (2016)
Infiltration is a process whereby the water from land surface infiltrate into the soil. Infiltration represent component of biggest water loss from precipitation source. Water infiltrate into the soil through pore spaces such as cracks and slit. The main objective of this study is to compare the infiltration rate that happen before and after the area being developed at two different places. This study also conducted to determine the types of soil at the particular area. The scope of work include the fieldwork and also at the laboratory work in order to gain the related data. The measurement of infiltration rate was taken and done at the site during sunny day because from of the El Nino phenomenon that hit Malaysia where started Mac 2015, peaked in December and the situation remained the same for the first three months of 2016. Its effects started to wane since late April and are expected to completely wear off by June 2016. The duration for this final project is until May 2016 so the infiltration rate of the areas during the rainy days cannot be determine. For the laboratory work, the types of the soil at both areas should be classified. The method used to determine the infiltration rate is by Double Ring Infiltrometer meanwhile the sieve analysis method used to obtain the types of the soil. The types of soil can be classified using the USDA textural classification. After the obtained data had been analysed, the infiltration rate of the two different places can be determine using the Horton method. Based on the types and characteristics of the soil exist at both developed and developed areas, the factors that affect the infiltration rate can be sort out.